Global trigger versatile module for ATLAS phase-II upgrade. (1st February 2023) - Filimonov, V.; Bauss, B.; Büscher, V.; Schäfer, U.; Ta, D.
Abstract: The Global Trigger Versatile Module (GVM) has been developed within the framework of the ATLAS detector Phase-II upgrade. The GVM acts as an auxiliary hardware component that can be used for development, testing and operational purposes within and beyond the ATLAS Global Trigger in projects requiring high bandwidth and processing capabilities. The module is designed to host an advanced Xilinx Ultrascale+ VU13P FPGA and Finisar BOA optical modules, running at high data rates up to 25.8 Gb/s, as well as other hardware resources needed for the Global Trigger, located on a high-density PCB, optimized for high-speed data transmission. A testing program of the Global Trigger Versatile Module includes verification of the main hardware functionality of the module, performance evaluation of the high-speed optical modules and the FPGA, and Global Common Module development firmware tests.